Penerapan Strategi Pembelajaran Billboard Ranking Guna Meningkatkan Prestasi Belajar Sejarah dalam Materi Perkembangan Masyarakat Indonesia Pada Masa Reformasi Pada Siswa Kelas XII SMA Negeri 3 Mandau Tahun Pelajaran 2021/2022 - Jumiati Jumiati (HEURISTIK: Jurnal Pendidikan Sejarah, 2022)
Learning strategy is a plan that contains a series of activities that are tailored to achieve certain educational goals. In the world of education there are many types of learning strategies used. Every learning strategy has its advantages and disadvantages. For this reason, every teacher must be able to choose the right learning strategy in delivering different materials so that the learning goals are achieved and maximized. For this reason, researchers want to research a Billboard Ranking learning strategy where learning activities are more considerate of students, students are given the widest opportunity to develop themselves, according to pieget, students must actively interact with their learning environment. This can help gain understanding for students.